Soil‐borne reservoirs of antibiotic‐resistant bacteria are established following therapeutic treatment of dairy calves. (21st December 2015) - Liu, Jinxin; Zhao, Zhe; Orfe, Lisa; Subbiah, Murugan; Call, Douglas R.
Summary: We determined if antibiotics residues that are excreted from treated animals can contribute to persistence of resistant bacteria in agricultural environments. Administration of ceftiofur, a third‐generation cephalosporin, resulted in a ∼ 3 log increase in ceftiofur‐resistant E scherichia coli found in the faeces and pen soils by day 10 ( P = 0.005). This resistant population quickly subsided in faeces, but was sustained in the pen soil (∼ 4.5 log bacteria g −1 ) throughout the trial (1 month). Florfenicol treatment resulted in a similar pattern although the loss of florfenicol‐resistant E . coli was slower for faeces and remained stable at ∼ 6 log bacteria g −1 in the soil. Calves were treated in pens where eGFP‐labelled E . coli were present in the bedding (∼ 2 log g −1 ) resulting in amplification of the eGFP E . coli population ∼ 2.1 log more than eGFP E . coli populations in pens with untreated calves (day 4; P < 0.005). Excreted residues accounted for > 10‐fold greater contribution to the bedding reservoir compared with shedding of resistant bacteria in faeces. Treatment with therapeutic doses of ceftiofur or florfenicol resulted in 2–3 log g −1 more bacteria than the estimated ID50 (2.83 CFU g −1 ), consistent with a soil‐borne reservoir emerging after antibiotic treatment that can contribute to the long‐term persistence of antibiotic resistance in animal agriculture.